Application of “Six Rights” on Medication Administration by Nurse and Patient Satisfaction - Imelda Rahmayunia Kartika; Vivi Melani (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2017)
Introduction: Giving the medications, nurse should pay attention to the principles of “six of rights", namely: right of patient, right medication, right dose, right way, right time, and right documentation. There are more than a half of nurses in a ward who are not provide medications in accordance with the Standard Operational Procedure  (SOP). The purpose of this study was to determine of the relationship between applications of Standard Operational Procedure  (SOP) six rights of medication administration by nurses and patient satisfaction. Methods: This study was using cross sectional design.There were 30 respondents taken by accidental sampling. This research was conducted in February 2017. Data collection used questionnaires and observation. Chi-Square test was used to analyze data. It can be known from 30 respondents who had six right in application of medication administration was performed good (50%) then respondents were satisfied (50%). Results: The results showed the significant relationship between the six rights of medication administration by nurse and the level of patient satisfaction (p = 0.003).Conclusion: It can be inferred that the higher interaction that occurs between nurse and patient in applying the principles of medication administration, it will higher patient satisfaction. Nurses suggested applying the six rights during medication administration.